Comprehensive assembly and analysis of the transcriptome of maritime pine developing embryos - Andreia S. Rodrigues; José J. De Vega; Célia M. Miguel (BMC Plant Biology, 2018)
Abstract Background There are clear differences in embryo development between angiosperm and gymnosperm species. Most of the current knowledge on gene expression and regulation during plant embryo development has derived from studies on angiosperms species, in particular from the model plant Arabidopsis thaliana. The few published studies on transcript profiling of conifer embryogenesis show the existence of many putative embryo-specific transcripts without an assigned function. In order to extend the knowledge on the transcriptomic expression during conifer embryogenesis, we sequenced the transcriptome of zygotic embryos for several developmental stages that cover most of Pinus pinaster (maritime pine) embryogenesis. Results Total RNA samples collected from five zygotic embryo developmental stages were sequenced with Illumina technology. A de novo transcriptome was assembled as no genome sequence is yet published for Pinus pinaster. The transcriptome of reference for the period of zygotic embryogenesis in maritime pine contains 67,429 transcripts, which likely encode 58,527 proteins. The annotation shows a significant percentage, 31%, of predicted proteins exclusively present in pine embryogenesis. Functional categories and enrichment analysis of the differentially expressed transcripts evidenced carbohydrate transport and metabolism over-representation in early embryo stages, as highlighted by the identification of many putative glycoside hydrolases, possibly associated with cell wall modification, and carbohydrate transport transcripts. Moreover, the predominance of chromatin remodelling events was detected in early to middle embryogenesis, associated with an active synthesis of histones and their post-translational modifiers related to increased transcription, as well as silencing of transposons. Conclusions Our results extend the understanding of gene expression and regulation during zygotic embryogenesis in conifers and are a valuable resource to support further improvements in somatic embryogenesis for vegetative propagation of conifer species. Specific transcripts associated with carbohydrate metabolism, monosaccharide transport and epigenetic regulation seem to play an important role in pine early embryogenesis and may be a source of reliable molecular markers for early embryogenesis.